Expedient screening for HIV-1 protease inhibitors using a simplified immunochromatographic assay - Kuntida Kitidee (2018)
© 2015 Elsevier B.V. A colloidal gold-based immunochromatographic (IC) strip test was developed and validated for the detection of HIV-1 protease (HIV-PR) activity and inhibitory effect of HIV-PR inhibitors (PIs). It is a unique 'two-step' process requiring the combination of proteolysis of HIV-PR and an immunochromatographic reaction. Monoclonal antibodies to the free C-terminus of HIV matrix protein (HIV-MA) conjugated to gold particles and a monoclonal antibody against intact and cleaved forms of the HIV-MA are immobilized on the 'Test'-line of the IC strip. Using lopinavir, a potent HIV protease inhibitor, the IC-strip was optimized to detect inhibitory activity against HIV-protease. At a lopinavir concentration of 1000 ng/mL (its suggested minimum effective concentration), a HIV-PRH6concentration of 6 mg/mL and incubation period of 60 min were the optimal conditions. A preliminary comparison between a validated high-performance liquid chromatography assay and the IC-strip to semi-quantify HIV protease inhibitor concentrations (lopinavir and atazanavir) demonstrated good agreement. This simplified method is suitable for the rapid screening of novel protease inhibitors for future therapeutic use. Moreover, the IC strip could also be optimized to semi-quantify PIs concentrations in plasma samples.